Chloro-benzoquinones cause oxidative DNA damage through iron-mediated ROS production in Escherichia coli. (September 2015) - Chen, Zhilan; Zhou, Qiaohong; Zou, Dandan; Tian, Yun; Liu, Biyun; Zhang, Yongyuan; Wu, Zhenbin
Highlights: CBQs have genotoxicity and cytotoxicity in E. coli cells. CBQs exposure to E. coli cells led to intracellular substantial ROS production. The addition of Fe 2+ to the CBQs exposure system enhanced DNA oxidative damage. ROS scavengers and iron-chelators can partial protect from oxidative DNA damage. AhpCF, catalase E and catalase G protected E. coli from DNA damage corporately. Abstract: Chloro-benzoquinones (CBQs) are a group of disinfection byproducts that are suspected to be potentially carcinogenic. Here, the mechanism of DNA damage caused by CBQs in the presence of ferrous ions was investigated in an Escherichia coli wild type M5 strain and a mutant L5 ( ahpCF katEG mutant) strain that carried an enhanced green fluorescent protein reporter under the control of a SOS response gene ( recA ) promoter. All tested CBQs (including para -benzoquinone, 2-chloro- para -benzoquinone, and dichloro- para -benzoquinones with different substitutes) caused substantial oxidative DNA damage with EC 50 values in the micromolar range. Moreover, 2, 5-dichloro- para -benzoquinone (2, 5-DCBQ), a typical CBQ, caused substantial ROS production in E. coli mutant cells. And ROS scavengers provided partial protective effects on genotoxicity of 2, 5-DCBQ to E. coli mutant cells. The addition of Fe 2+ to the 2, 5-DCBQ exposure system caused an increase in DNA oxidative damage; iron-chelating agents could partially prevent these cells from DNA damage. Finally, intracellular AhpCF, catalase E, and catalase G were all found to play an important role in the survival of E. coli cells exposed to CBQs, as indicated by an increased sensitivity of the ahpCF katEG mutant L5 strain to treatment compared with wild type M5 cells. Taken together, these results suggest that CBQs cause oxidative DNA damage in E. coli cells through the participation of iron-mediated ROS production.